Marx, the State, and the Tendency of the Rate of Profit to Fall (Temporalis, 2026)
This article presents a critical analysis, grounded in the Marxist framework, of the declining trend in the profit rate and the role of the State in mobilizing countertendencies to mitigate it. Drawing upon a reconstruction of Marx’s theoretical development, from his early formulations to the conceptual maturity evident in Capital, the study examines key categories such as capitalist accumulation and the organic composition of capital, situating them in dialogue with Mészáros’s work on structural crisis. The central argument is that the decline in profitability represents a structural determination intrinsic to the dynamics of capital, whose consequences are addressed through state-led mechanisms counteracting the tendency of the profit rate to fall. Methodologically, the study is based on a systematic literature review conducted within the Social Work program at the Federal University of Paraíba between 2023 and 2025.
Keywords: State; Structural crisis; Tendency of falling profit rate